The productivity of performing art organisations versus labor costs - Smolny, Katarzyna; Gałecka, Małgorzta (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The study of the problem of “cost disease” contributes to the possibility of creating a model for effective subsidy to cultural institutions operating in the field of performing arts from public funds. The study also forms a part of a broader reflection on the values of culture, the humanism of culture and the economy in general. Aim: This article is to examine the connection between productivity and labor costs in public theatres in Poland. We investigate what the level of productivity depends on. We check whether it is based on costs or the so-called income gap or another factor. We verify whether costs in PAOs in Poland increase according to the theory of Baumol’s cost disease and whether labor costs are particularly significant in total costs. Results: Labor costs should be taken into account when subsidizing performing art organizations, as productivity growth depends on having funds to cover labor costs and increasing employment.